2020
DOI: 10.1021/acs.biomac.0c01147
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Structural Integrity and Mechanical Properties of Globular Protein Vesicles by Blending Crosslinkable and NonCrosslinkable Building Blocks

Abstract: Vesicles made from functionally folded, globular proteins that perform specific biological activities, such as catalysis, sensing, or therapeutics, show potential applications as artificial cells, microbioreactors, or protein drug delivery vehicles. The mechanical properties of vesicle membranes, including the elastic modulus and hardness, play a critical role in dictating the stability and shape transformation of the vesicles under external stimuli triggers. Herein, we have developed a strategy to tune the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 42 publications
(111 reference statements)
0
15
0
Order By: Relevance
“…SDS-PAGE analysis suggested that C-PC was also covalently modified by UV irradiation in a pH-dependent manner (see Figure S11A for details). Generally, photo-crosslinking in proteins often occurs between several photoactive residues, such as Cys, His, Trp, and Tyr, forming disulfide, histidine–lysine, or dityrosine linkages. In our case, the photo-crosslinkingoccurred intermolecularly via nonreducible covalent bondsmost likely involves Tyr residues, given their high abundance in C-PC relative to the other photoactive residues (Figure S3A). Moreover, it was noticed that most of the Tyr residues in C-PC locate around the chromophores and at the interfaces across α- and β-subunits (Figure ), making it possible for the photo-crosslinking to happen intermolecularly across separate chains, as was suggested by SDS-PAGE gels.…”
Section: Resultsmentioning
confidence: 79%
“…SDS-PAGE analysis suggested that C-PC was also covalently modified by UV irradiation in a pH-dependent manner (see Figure S11A for details). Generally, photo-crosslinking in proteins often occurs between several photoactive residues, such as Cys, His, Trp, and Tyr, forming disulfide, histidine–lysine, or dityrosine linkages. In our case, the photo-crosslinkingoccurred intermolecularly via nonreducible covalent bondsmost likely involves Tyr residues, given their high abundance in C-PC relative to the other photoactive residues (Figure S3A). Moreover, it was noticed that most of the Tyr residues in C-PC locate around the chromophores and at the interfaces across α- and β-subunits (Figure ), making it possible for the photo-crosslinking to happen intermolecularly across separate chains, as was suggested by SDS-PAGE gels.…”
Section: Resultsmentioning
confidence: 79%
“…8,[12][13][14][15] Protein vesicles or proteinosomes, consisting of fully folded, functional globular proteins, have recently attracted attention due to their expected biological properties, including biocompatibility and specific protein activities in vesicle structure, useful for microbioreactors, drug delivery vehicles, and synthetic protocells. 3,[16][17][18][19] Particularly, globular protein vesicles (GPVs) can be made through self-assembly of recombinant fusion proteins consisting of fully folded, globular proteins and intrinsically disordered polypeptides in benign aqueous environments at room temperature. 16,17 Since this fabrication is favorable to biological molecules and processes, GPVs can offer diverse biochemical functionality and tunability.…”
Section: Introductionmentioning
confidence: 99%
“…34 Due to the behavior of ELPs, self-assembly of vesicles is dependent on ionic strength, protein concentration, temperature, and composition of the ELP guest residue. 29,34,36 Vesicle self-assembly also depends on the characteristics of the globular protein due to the molecular packing constraints of the amphiphiles including the molar ratio of globule-Z E to Z R -ELP (Z E /Z R ratio). 31,32 Here, we incorporated the ionizable amino acid histidine into the guest residue of ELP to develop pH-sensitive vesicles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The vesicles are composed of a single layer with a hydrophilic shell of globular protein on the exterior and hydrophobic ELP on the interior . Due to the behavior of ELPs, self-assembly of vesicles is dependent on ionic strength, protein concentration, temperature, and composition of the ELP guest residue. ,, Vesicle self-assembly also depends on the characteristics of the globular protein due to the molecular packing constraints of the amphiphiles including the molar ratio of globule-Z E to Z R -ELP (Z E /Z R ratio). , …”
Section: Introductionmentioning
confidence: 99%